Lithospheric diamond formation as a consequence of methane-rich volatile flooding: An example from diamondiferous eclogite xenoliths of the Karelian craton (Finland). (1st June 2017) - Smart, K.A.; Cartigny, P.; Tappe, S.; O'Brien, H.; Klemme, S.
Abstract: A collection of 61 xenocrystic and 12 eclogite xenolith-derived diamonds from the 600 Ma Lahtojoki kimberlite in central Finland has been investigated. Calculated pressure and temperature conditions for the diamondiferous eclogites are in excess of 5.5 GPa and 1300 °C, suggesting residence depths greater than 180 km, near the base of the Karelian cratonic mantle lithosphere. Geochemically, the eclogite xenoliths have gabbroic compositions showing positive Eu and Sr anomalies, relatively low ΣREE and elevated Al2 O3 contents, yet garnets have ambiguous δ 18 O values of 5.7‰ and 5.9‰. Gabbroic eclogite formation could therefore be linked to either subduction processes during the 1.9 Ga Svecofennian orogeny or to cumulate processes during 2.1 Ga rift-induced magmatism. Determination of the oxygen fugacity of Lahtojoki eclogite xenoliths from both this work and previous studies suggests that diamond-bearing eclogites may be more reduced (ΔFMQ-3.5) compared to barren eclogites (ΔFMQ-1.7). While recycled oceanic crust protoliths for the eclogites remain a possibility, the carbon isotopic compositions and nitrogen abundances of the Lahtojoki diamonds indicate mantle-derived volatile sources. All diamonds (i.e., loose and eclogite xenolith-derived) display a restricted range of δ 13 C values from −7.8‰ to −3.7‰ that overlaps with the carbon isotopic composition of Earth's mantle. The Lahtojoki diamond δ 13 C values form a negatively skewed distribution, indicating diamond growth from reduced mantle-derived carbon sources such as methane- (CH4 ) bearing fluids. Nitrogen contents of the Lahtojoki diamonds range from 40 to 1830 atomic ppm with a mean of ∼670 atomic ppm; these elevated nitrogen contents combined with the close association to eclogites suggest an eclogitic or crustal volatile source. However, the Karelian craton was periodically intruded by ultramafic alkaline magmas since at least 1.8 Ga, noting in particular the occurrence of phlogopite-rich kimberlites and olivine lamproites between 1200 and 700 Ma. We argue that this punctuated volatile-rich magmatism simultaneously metasomatised the cratonic mantle lithosphere, forming nitrogen enriched phlogopite-bearing metasomes. We propose that reduced, carbon-bearing and nitrogen-rich fluids were remobilized to form the Lahtojoki diamonds. The diamond-forming event(s) most probably occurred during or shortly prior to the entraining kimberlite magmatism as indicated by the diamond nitrogen aggregation systematics. Involvement of reduced diamond-forming fluids is supported by both the negative skewness of Lahtojoki diamond δ 13 C values and the more reduced nature of the diamondiferous Lahtojoki eclogites compared with their more oxidized barren counterparts. Our results from the diamondiferous eclogites derived from the deepest parts of the Karelian cratonic mantle root are in support of methane being the stable carbon volatile species at the base of thick continental lithosphere.